Strategi Pembelajaran Anak Usia Dini Berbasis Multiple Intelligence - Habibi, Yuliana; ., Srifariyati; Hasan, Hafiedh (Madaniyah, 2017)
Gardner explains that intelligence is some of the abilities that a person possesses, which will not all be equal to the abilities others have, because they are of many types, Gardner calls them multiple intelligences. The development of learning strategy is intended to provide an alternative paradigm in order to prepare PAUD/TK/RA teachers who have special skills in early childhood education. Therefore, further research on the effectiveness of early childhood learning strategies based on multiple intelligences was developed to improve the competence of RA teachers. The research method used experiments, involving 116 RA teachers in Pemalang district. Data analysis used statistical analysis of Paired Sample T-Test, which aims to find out the effectiveness of AUD based learning strategy based on multiple intelligence in improving the competence of PAUD/TK/RA teachers. The results showed the significance of paired sample t-test of 0.000 (<0.05) with a t value of 9.555. Thus, the results of the analysis show that statistically, the effectiveness of early childhood learning strategies based on mulitple intelligence in improving the competence of RA teachers is tested.Â Keywords: Learning Strategy Multiple Intelligence, Teacher Competence